2013
DOI: 10.1111/acer.12155
|View full text |Cite
|
Sign up to set email alerts
|

A Corn Oil–Based Diet Protects Against Combined Ethanol and Iron‐Induced Liver Injury in a Mouse Model of Hemochromatosis

Abstract: A CO-based diet is protective against combined EtOH- and iron-induced liver toxicity, likely via attenuation of hepatic steatosis and oxidative stress and may have a role in the prevention of fibrosis development in chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
8
0
2
Order By: Relevance
“…Supporting this notion it has been reported that mice fed with corn oil-based diet for 8 weeks displayed hepatoprotection against ethanol and iron-induced liver injury. This could be attributed to attenuation of hepatic oxidative stress and steatosis, preservation of the enzymatic antioxidant defence system (CAT, GPx), modulation of the inflammatory cascade and fibrogenic pathways, protecting against liver fibrosis (Tan et al 2013). However, we did not observe such improvement in liver functions and structure in the BPA group although it was dissolved in the same dose of corn oil as in the vehicle control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this notion it has been reported that mice fed with corn oil-based diet for 8 weeks displayed hepatoprotection against ethanol and iron-induced liver injury. This could be attributed to attenuation of hepatic oxidative stress and steatosis, preservation of the enzymatic antioxidant defence system (CAT, GPx), modulation of the inflammatory cascade and fibrogenic pathways, protecting against liver fibrosis (Tan et al 2013). However, we did not observe such improvement in liver functions and structure in the BPA group although it was dissolved in the same dose of corn oil as in the vehicle control group.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to attenuation of hepatic oxidative stress and steatosis, preservation of the enzymatic antioxidant defence system (CAT, GPx), modulation of the inflammatory cascade and fibrogenic pathways, protecting against liver fibrosis (Tan et al 2013). Supporting this notion it has International Journal of Experimental Pathology, 2016, 97, 369-379 been reported that mice fed with corn oil-based diet for 8 weeks displayed hepatoprotection against ethanol and iron-induced liver injury.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…A corn oil–based diet protects against combined alcohol- and iron-induced mild steatohepatitis and portal–portal tract linkage fibrosis and increases the levels of AMPK, which is low in mice hepatic fibrosis models. This suggests that AMPK has a preventative role in fibrosis arising from alcoholic steatohepatitis [ 71 ]. Moderate obesity plus alcohol intake cause pericellular fibrosis and synergistic steatohepatitis in an alcohol dose-dependent manner whereas adiponectin increases the levels of AMPK and reverses these effects [ 72 ].…”
Section: Protection Of Ampk Against Hepatic Fibrosis By Various Causementioning
confidence: 99%
“…CCl 4 , also known as tetrachloromethane, is an organic compound that induces hepatic fibrosis in experimental animals. In the CCl 4 mouse model, AMPK suppresses the expression of Nox4, TGF-β, and α-SMA and restrains the proliferation of HSC in a dose- and time-dependent manner [ 71 ]. ADP355 can attenuate CCl 4 -induced hepatic fibrosis via AMPK signaling.…”
Section: Protection Of Ampk Against Hepatic Fibrosis By Various Causementioning
confidence: 99%
“…For instance, ethanol enhances fatty acid synthesis in hepatocytes through the upregulation of sterol regulatory element binding protein 1c (SREBP-1c) protein expression, which induces a battery of lipogenic enzymes [ 4 ]. In addition, alcohol promotes lipid accumulation by inhibiting peroxisome proliferator-activated receptor- α (PPAR- α ) and adenosine monophosphate-activated protein kinase (AMPK), which have been investigated to control the transcription of a range of genes involved in free fatty acid transport and oxidation [ 5 , 6 ]. Moreover, Gao reported that adiponectin and tumor necrosis factor- α (TNF- α ) suppress mutual gene expression and antagonize their biological effects in the liver tissues [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%